The Impacts of Inflation, Economic Growth and Labor Wage on Open Unemployment - Fransiskus X Lara Aba; Elisabeth Magdalena (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
This study aims to analyze the impacts of inflation, economic growth (GDP), and labor wages on open unemployment in Indonesia for the period 2008-2016. The method of analysis used is a multiple linear regression with classical test and hypotheses. The results show that, partially, each of these three factors, as the only independent variables, does not have a significant effect on the open unemployment rate as the dependent variable. The regression model also shows no autocorrelation and heterocedasticity issues. While with all factors as a whole, the result shows that there is a simultaneously significant influence of the three fators on the open unemployment rate.